The Importance of Communication in Islamic Society - Maryani, Maryani (International Conference of Moslem Society, 2018)
Communication is an integral part of human life because our movements are always associated by communication. At this point, the communication is in terms of Islamic communication, i.e. communication of moral al-karimah or ethics. Communication of morality means the communication that comes from the Quran and hadith (sunnah of the Prophet). Islamic communication is a new form of phrase and thought emerged in academic research started from about three decades ago. The emergence of Islamic communication thoughts and activism is based on the failure of the philosophy, paradigm and implementation of western communication which further optimizes the pragmatic, materialistic and capitalist media values. This failure has negative implications especially on the Muslim community throughout the world due to the different religions, cultures and lifestyles of the (western) countries that are as the producers of the sciences. There are two kinds of communication consisting of: (1) direct communication (face to face) either between individual with individual, or individual with group, or group with group, group with society, hence influence the individual relation (interpersonal) included in understanding the communication; and (2) mass communication that is a process of communication made through the mass media with various purposes of communication and to convey information to a wide audience. The basics of communication principles must be mastered. By mastering the principles of communication in Islamic society, it can be able to organize Islamic education and Islamic communication to form a high-quality communication in the society, professionals, and noble character.